GDF11 Alleviates Pathological Myocardial Remodeling in Diabetic Cardiomyopathy Through SIRT1-Dependent Regulation of Oxidative Stress and Apoptosis - Zhu, Han-Zhao; Zhang, Li-Yun; Zhai, Meng-En; Xia, Lin; Cao, Yu; Xu, Lu; Li, Kai-Feng; Jiang, Li-Qing; Shi, Heng; Li, Xiang; Zhou, Ye-Nong; Ding, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Growth differentiation factor 11 (GDF11) is a member of the transforming growth factor β superfamily that alleviates cardiac hypertrophy, myocardial infarction, and vascular injury by regulating oxidative stress, inflammation, and cell survival. However, the roles and underlying mechanisms of GDF11 in diabetic cardiomyopathy (DCM) remain largely unknown. In this study, we sought to determine whether GDF11 could prevent DCM. After establishing a mouse model of diabetes by administering a high-fat diet and streptozotocin, intramyocardial injection of an adeno-associated virus was used to achieve myocardium-specific GDF11 overexpression. GDF11 remarkably improved cardiac dysfunction and interstitial fibrosis by reducing the levels of reactive oxygen species and protecting against cardiomyocyte loss. Mechanistically, decreased sirtuin 1 (SIRT1) expression was observed in diabetic mice, which was significantly increased after GDF11 overexpression. To further explore how SIRT1 mediates the role of GDF11, the selective inhibitor EX527 was used to block SIRT1 signaling, which abolished the protective effects of GDF11 against DCM. In vitro studies confirmed that GDF11 protected against H9c2 cell injury in high glucose and palmitate by attenuating oxidative injury and apoptosis, and these effects were eliminated by SIRT1 depletion. Our results demonstrate for the first time that GDF11 protects against DCM by regulating SIRT1 signaling.